Intereference of storage temperatures in the development of mesophilic, psychrotrophic, lipolytic and proteolytic microbiota of raw milk - Luana Martins Perin (Semina: Ciências Agrárias, 2012)
With the objective of comparing distinct storage conditions of raw milk, 20 samples of raw milk were collected, and portions of each were stored at different storage conditions (4°C for 48 h, 7°C for 48 h and 25°C for 4 h). Populations of mesophilic aerobes and psychrotrophics (total, lipolytic and proteolytic) were monitored, and the results were compared by analysis of variance (ANOVA, P < 0.05). Psychrotrophics were randomly selected and identified. Mesophilic aerobes had significant development after 48 h at 7°C and 25°C. For psychrotrophics, the differences were evident in samples with high levels of initial contamination. Pseudomonas and Serratia were the main species of contamination. The storage conditions of raw milk allowed the development of spoilage psychrotrophics, which were more evident in samples with low microbiological quality.